2018
DOI: 10.3390/nu11010028
|View full text |Cite
|
Sign up to set email alerts
|

Navy Beans Impact the Stool Metabolome and Metabolic Pathways for Colon Health in Cancer Survivors

Abstract: Colorectal cancer (CRC) is the third leading cause of cancer-related death in the United States and emerging evidence supports that increased consumption of legumes, such as navy beans, can reduce risk. Navy bean consumption was previously shown to modulate host and microbiome metabolism, and this investigation was performed to assess the impact on the human stool metabolome, which includes the presence of navy bean metabolites. This 4-week, randomized-controlled trial with overweight and obese CRC survivors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 66 publications
2
40
1
Order By: Relevance
“…Linoleic acid metabolism and arachidonic acid metabolism are two acid metabolism-related pathways that were also significantly activated in KRT High OSCC tumor groups. Acid metabolism have been extensively proved to be associated with cancer initiation and progression [28][29][30] by previously studies. Linoleic acid and arachidonic acid were the two acids that specifically identified in the present study, whose metabolism might be dysregulated by aberrant KRT84 expression, so this should also be potential pathways by which KRT84 could regulate OSCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Linoleic acid metabolism and arachidonic acid metabolism are two acid metabolism-related pathways that were also significantly activated in KRT High OSCC tumor groups. Acid metabolism have been extensively proved to be associated with cancer initiation and progression [28][29][30] by previously studies. Linoleic acid and arachidonic acid were the two acids that specifically identified in the present study, whose metabolism might be dysregulated by aberrant KRT84 expression, so this should also be potential pathways by which KRT84 could regulate OSCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Navy beans and their metabolites (Table 1) have been implicated in the protection of CRC through the modulation of major metabolic pathways like lysine, sterol, amino and inositol, and fatty acid metabolism. Dietary intake of navy beans (35 g/day) has been found to increase the abundance of several amino acids in stools, showing a protective effect against CRC through the inhibition of cellular progression, reduction of oxidative stress, and induction of cellular apoptosis [192,193]. A study performed on 16 people (seven non-cancer subjects and nine CRC survivors) has shown that the addition of 35 g cooked navy bean powder in meals for 28 days is able to provide chemoprevention effects against CRC [194].…”
Section: P-coumaric Acidmentioning
confidence: 99%
“…(Navy bean) Beans Anacardic acid ( Figure 8e) and nobiletin Imparts glutathione regulation, and involved cancer control mechanisms such as detoxification of xenobiotics, antioxidant defense, proliferation, and apoptosis. Metabolic pathways involving lysine, and phytochemicals were also modulated by navy bean intake in CRC survivors [465]. Anacardic acid efficiently repressed expression of CD44 and MMP14 in HCT116 colon cancer cells, with repression of the SUMOconjugated TFAP2A isoform and elimination of CD44+/hi/ALDH+/hi cells [466].…”
Section: Phaseolus Vulgarismentioning
confidence: 99%